SOME COMMON FIXED POINT THEOREM USING OCCASIONALLY WEAKLY COMPATIBLE AND RECIPROCAL CONTINUITY IN INTUITIONISTICFUZZY METRIC SPACES - et al., Krishnaveni S (International Journal of Advanced Science and Technology, 2019)
We are proving some common fixed point theorem using two notations occasionally weakly compatible and reciprocal continuity in intuitionistic fuzzy metric spaces.